Pendekatan Spiritual Dan Herbal Sebagai Alternatif Rehabilitasi Non Medis Bagi Pecandu Narkoba - agoeng noegroho; Adhi Iman Sulaiman; Bambang Suswanto; Suryanto Suryanto (Institut Agama Islam Negeri Kendari, 2018)
The study aimed to analyze spiritual and herbal approaches as an alternative to non-medical rehabilitation for drug addicts. The research location was in Nurul Ichsan Al Islami and An-Nur homes in Purbalingga Regency using Participatory Learning and Action (PLA) methods. Determination of purposively selected informants is namely administrators of the foundation, former drug addicts who are in the process of rehabilitation and assistants or counselors. Data collection was conducted through interviews, observation, Focus Group Discussion (FGD) and it is found that the Nurul Ichsan Al Islami and An-Nur Foundations could be used as alternatives in spiritual and herbal drug abuse rehabilitation (non-medical). Spiritual rehabilitation uses a humanist, familial and dialogical approach so that drug addicts can be open, feel close and build their trust in the counselor in the process of therapy. Spiritual rehabilitation is carried out by restoring human nature to faith and piety by worship, loving family and friends, endeavoring and socializing through da'wah therapy, prayer, recitation and dhikr in congregation, doing rukiyah to fight the addiction with bathing therapy in river and boiled water (godog) accompanied by prayer, then rehabilitate herbs with potions like herbs for vitality and poison detoxification.